Optimizing harvesting for facial lipografting with a new photochemical stimulation concept: One STEP technique™ - Centurión, Patricio (2020)
Background: Facial fat grafting for rejuvenation is one of the most popular facial aesthetic procedures in plastic surgery. It is always challenging and since there are a lot of techniques for adipose tissue (AT) harvesting, there are no standard procedures that guarantee natural and long-lasting results. We developed the selective tissue engineering photo stimulation technique (One STEP™) in which we used a novel infrared 1210-nm wavelength laser diode for fat preserved harvesting and direct fat injection that we named PicoGraft™, with no fat manipulation. Methods: This is a retrospective descriptive study in which we included all senior author’s patients that got facial fat grafting using the One STEP™ technique. We compared the AT aspirated, after laser emission (STEP-PicoGraft) and the standard assisted liposuction samples (SAL) in cultures. We study the mitochondrial activity of the ASC between STEP and SAL in fresh samples and after 24 h. The evaluation of the results included subjective changes regarding wrinkles, grooves, palpebral bags, hyperchromic spots, and fat hypotrophy of our patients. Results: Between July 2013 and May 2018, a total of 245 patients underwent facial fat grafting using this novel technique. We observed adipocytes preserved after STEP harvesting comparing morphologic changes in SAL samples with a high concentration of inflammatory particles in cultures. ASC mitochondrial activity shows an important difference of more than 7 times in STEP samples in fresh analysis that increase 12 times in 24 h. The subjective results show a good improvement in the periorbital area. The changes on the skin and subcutaneous tissue are seen from the second month and continue to improve up to 12 months. Conclusions: Facial fat grafting using the PicoGraft™ obtained by One STEP™ technique gives excellent volumetric and regenerative results in a single treatment without volumetric hypercorrection, and it is a good alternative for facial rejuvenation. The fat graft obtained with this novel technique is homogenous, without lumps, and has high concentration of viable stimulated ADSC and a high number of viable adipocytes. Level of evidence: Level III, therapeutic study.